Targeting the brain lesions using peptides: A review focused on the possibility of targeted drug delivery to multiple sclerosis lesions. (May 2021) - Rayatpour, Atefeh; Javan, Mohammad
Graphical abstract: Abstract: As described by Jean Martin Charcot in 1868, multiple sclerosis (MS) is an inflammatory, demyelinating and neurodegenerative disease of the central nervous system (CNS) which leads to permanent disability in patients. Following CNS insults, astrocytes and microglial cells undergo changes, which lead to scar formation in the site of injury. Owning to the pathophysiology of MS lesions, changes in both cellular and extracellular matrix (ECM) components occur over the progression of disease. In spite of advances in therapeutic approaches, drug delivery to MS lesions appears of great interest with big challenges and limitations. Targeting with peptides is a novel promising approach in the field of drug delivery. Recently peptides have been used for active targeting of different pathological disorders in which specific peptides make targeted accumulation of cargos to enhance local drug concentration at the pathological area, lead to increased therapeutic efficacy and decreased side effects. However, specific approaches for targeting the lesion in MS are still lacking. In this review, we discuss the changes of the ECM components as well as the cellular characteristics of demyelinated lesions and emphasis on opportunities for peptide based targeted drug delivery to highlight the possibility of such approaches for neurodegenerative disease with specific focus on MS.